The challenge of acute coronary syndromes in South Africa - Manga, Pravin (SA Heart Journal, 2017)
Atherosclerotic coronary artery disease remains highly prevalent in South Africa. Whereas in the past the disease predominantly affected the white and Indian population groups, there is a slow but steady rise in the prevalence of coronary artery disease in the black African population.